2021
DOI: 10.1002/lt.26032
|View full text |Cite
|
Sign up to set email alerts
|

Renal Outcomes After Simultaneous Liver‐Kidney Transplantation: Results from the US Multicenter Simultaneous Liver‐Kidney Transplantation Consortium

Abstract: Simultaneous liver-kidney transplantation (SLKT) is increasingly common in the United States. However, little is known about the renal-related outcomes following SLKT, which are essential to maximize the health of these allografts. We examined the factors impacting renal function following SLKT. This is an observational multicenter cohort study from the US Multicenter SLKT Consortium consisting of recipients of SLKT aged ≥18 years of transplantations performed between February 2002 and June 2017 at 6 large US … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Indeed, regarding KDPI, the literature indicates a cut-off of 70% for increased risk of developing kDGF and worsening outcomes [ 14 , 47 ]. Similarly, the survival advantage conferred by CLKT compared to LTA decreases with the utilization of grafts with a higher KDPI, as demonstrated by Sharma et al [ 48 ].…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, regarding KDPI, the literature indicates a cut-off of 70% for increased risk of developing kDGF and worsening outcomes [ 14 , 47 ]. Similarly, the survival advantage conferred by CLKT compared to LTA decreases with the utilization of grafts with a higher KDPI, as demonstrated by Sharma et al [ 48 ].…”
Section: Discussionmentioning
confidence: 85%
“…In the multivariable Cox analysis, the independent risk factors associated with CKD stages 4 to 5 were DGF (HR, 1.72; 95% CI, 1.10-2.71), NASH (HR, 1.58; 95% CI, 1.01-2.45), and recipient pre-SLKT DM (HR, 1.45; 95% CI, 1.00-2.15), whereas the use of tacrolimus (HR, 0.44; 95% CI, 0.22-0.89) decreased the risk. (25) Despite the increased risk for advanced CKD, DGF did not impact overall patient survival. Our larger cohort study found similar overall DGF rates (21%) among SLKT recipients; however, DGF was significantly higher in recipients on pretransplant dialysis and among those who received AKI kidneys (up to 50%).…”
Section: Discussionmentioning
confidence: 96%
“…In the current issue of Liver Transplantation , Sharma and colleagues report the results of an observational multicenter cohort study from the US Multicenter SLKT consortium of adult SLKT recipients across 6 large US centers. ( 5 ) During 5 years of follow‐up after SLKT, 68% of patients developed ≥stage 3 CKD and 16% developed stage 4‐5 CKD. Risk factors for post‐LT stage 4‐5 CKD included baseline diabetes mellitus, nonalcoholic steatohepatitis (NASH), and delayed kidney graft function.…”
Section: Center Variationmentioning
confidence: 99%